Comprehensive Details on Human Papillomavirus (HPV) Infections and Associated Malignancies: Awareness about Prophylaxis & Treatment Options Available for HPV Infections - Gul, Somia; Batool, Zaira; Bano, Samiah; Aziz, Aisha; Tanveer, Syeda Hamna (Bangladesh Journal of Medical Science, 2024)
Human Papilloma virus (HPV) role has now been widely accepted as a causative agent for cervical as well as head and neck squamous cell carcinomas. Screening and early detection of cervical cancer remains the key element to eradicate this deadly disease. Since it has a long natural history and disease progression, this gave an opportunity for early detection through screening of precancerous lesions which was adopted in high income countries (HIC) like UK which has led to the significant reduction of the cases. Unfortunately, Low- and middle-income countries are facing huge burden because of the lack of effective screening program. FDA approved Cervarix, Gardasil and Gardasil 9 are used as prophylaxis for cervical cancer & genital warts but screening is still essential after vaccination because these vaccines are not effective against all types of HPV types. HPV 16 & HPV 18 are highly oncogenic types and accounts for 70% of cervical cancers. The use of vaccine reduces the risk of getting HPV infection and decrease the rate of morbidity and mortality due to the cervical cancer. In addition to vaccines, many peptides or protein-based & cell or DNA-based vaccines are still in clinical trials; these prevention and management available in vaccines are likely to come up with significant benefits of health in future. Although it’s usually cured by immune system but presence of certain cofactors such as smoking, HIV etc. reduces the probability of an individual to eradicate the infection effectively. The aim of this study is to review literature regarding HPV related infections and malignancies. Moreover, it will make individuals aware about prophylaxis & treatment options available for HPV infection. This review article evaluates the HPV related diseases, there screening, evaluation and management currently available. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 967-983